LAPAROSCOPIC CHOLECYSTECTOMY IN ACUTE GALL BLADDER - Masood, Rehan; ., Samillah; Afridi, Zia ud Din; Masood, Kamran; Khan, Basharat Ali; Khurshied, Fezan (Journal of Postgraduate Medical Institute, 2012)
Objective: To look for the feasibility and results of laparoscopic cholecystectomy in acutely inflamed gallbladder, gangrenous cholecystitis and empyema gall bladder. Methodology: It was a prospective observational case series. As an institutional policy early laparoscopiccholecystectomy was performed in all the patients with diagnosis of acute cholecystitis. The incidence ofgangrenous cholecystitis and empyema gall bladder was noted and laparoscopic intervention was preferredin all these patients. The demographic profile, clinical records, operative details, complications and followup details were prospectively gathered on a performa. Results: Early laparoscopic cholecystectomy was performed in 142 patients. 103 patients had simple acutecholecystitis, 13 patients had empyema gall bladder and 26 patients had gangrenous cholecystitis. Theincidence of comorbids such as diabetes mellitus, hypertension and ischemic heart diseases was 28.1%,61.5 and 80.75 in patients with simple acute cholecystitis, empyema gall bladder and gangrenouscholecystitis respectively. Male gender was predominating in patients with complicated cholecystitis. Theopen conversion rate was 3.88% in simple acute cholecystitis, 15.38% in empyema gall bladder andgangrenous cholecystitis combined. There were 2 major complications in patients with simple acutecholecystitis and 2 major complications in patients with gangrenous cholecystitis. There was one mortalityin a patient with simple acute cholecystitis. Conclusion: Laparoscopic cholecystectomy is a safe and effective option in acute gall bladder. Based onour experience we recommend an early laparoscopic gall bladder removal, provided expertise & gadgetsare available.